In vivo wide-field reflectance/fluorescence imaging and polarization-sensitive optical coherence tomography of human oral cavity with a forward-viewing probe - Yoon, Yeoreum (Biomed Opt Express, 2015)
We report multimodal imaging of human oral cavity in vivo based on simultaneous wide-field reflectance/fluorescence imaging and polarization-sensitive optical coherence tomography (PS-OCT) with a forward-viewing imaging probe. Wide-field reflectance/fluorescence imaging and PS-OCT were to provide both morphological and fluorescence information on the surface, and structural and birefringent information below the surface respectively. The forward-viewing probe was designed to access the oral cavity through the mouth with dimensions of approximately 10 mm in diameter and 180 mm in length. The probe had field of view (FOV) of approximately 5.5 mm in diameter, and adjustable depth of field (DOF) from 2 mm to 10 mm by controlling numerical aperture (NA) in the detection path. This adjustable DOF was to accommodate both requirements for image-based guiding with high DOF and high-resolution, high-sensitivity imaging with low DOF. This multimodal imaging system was characterized by using a tissue phantom and a mouse model in vivo, and was applied to human oral cavity. Information of surface morphology and vasculature, and under-surface layered structure and birefringence of the oral cavity tissues was obtained. These results showed feasibility of this multimodal imaging system as a tool for studying oral cavity lesions in clinical applications.